2018
DOI: 10.1093/gerona/gly034
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cardiovascular Function in Old Mice After N-Acetyl Cysteine and Glycine Supplemented Diet: Inflammation and Mitochondrial Factors

Abstract: Metabolic, inflammatory, and functional changes occur in cardiovascular aging which may stem from oxidative stress and be remediable with antioxidants. Glutathione, an intracellular antioxidant, declines with aging, and supplementation with glutathione precursors, N-acetyl cysteine (NAC) and glycine (Gly), increases tissue glutathione. Thirty-month old mice were fed diets supplemented with NAC or NAC+Gly and, after 7 weeks, cardiac function and molecular studies were performed. The NAC+Gly supplementation impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 53 publications
(64 reference statements)
0
20
0
Order By: Relevance
“…A recent study by Cieslik and colleagues showed that combined treatment with glutathione precursors, N-Acetyl Cysteine (NAC) and Glycine, but not NAC alone, can reverse age-related diastolic dysfunction ( Cieslik et al, 2018 ). While the study suggests that aged mice may benefit from increased glutathione content, the effects of the combined treatment on in vivo cardiac glutathione contents and S-glutathionylation remain to be established.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Cieslik and colleagues showed that combined treatment with glutathione precursors, N-Acetyl Cysteine (NAC) and Glycine, but not NAC alone, can reverse age-related diastolic dysfunction ( Cieslik et al, 2018 ). While the study suggests that aged mice may benefit from increased glutathione content, the effects of the combined treatment on in vivo cardiac glutathione contents and S-glutathionylation remain to be established.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Cieslik and colleagues showed that combined treatment with glutathione precursors, N-Acetyl Cysteine (NAC) and Glycine, but not NAC alone, can reverse age-related diastolic dysfunction 35 . While the study suggests that aged mice may benefit from increased glutathione content, the effects of the combined treatment on in vivo cardiac glutathione contents and S-glutathionylation remain to be established.…”
Section: Targeting Mitochondrial Oxidative Stress In Late-life Reversmentioning
confidence: 99%
“…The effects of NAC were greatest, achieving an almost two-fold increase in plasma GSH levels [38]. In addition, NAC supplementation was found to benefit individuals with low resting GSH levels [74], and may be even more effective when supplemented with glycine [75].…”
Section: Effect Of Individual Amino Acid Supplementationmentioning
confidence: 99%